PROTECTIVE ROLE OF LYCOPENE ON BISPHENOL A INDUCED CHANGES IN SPERM CHARACTERISTICS, TESTICULAR DAMAGE AND OXIDATIVE STRESS IN RATS - P. TAMILSELVAN,; K. BHARATHIRAJA,; S.VIJAYAPRAKASH,; M.P. BALASUBRAMANIAN, (International Journal of Pharma and Bio Sciences, 2013)
Bisphenol A (BPA) is an estrogenic environmental toxicant, a synthetic monomer widely used to polymerize polycarbonate plastics and resins. BPA has been implicated to have hazardous effect on reproductive health in human and experimental rats. Lycopene is a powerful antioxidant and potential high-value compound for the prevention of many diseases. The present study has been designed to investigate the protective role of lycopene on BPA induced body and organ weight, sperm count, sperm motility, antioxidant enzymes levels, oxidative stress levels and histopathological studies in rats. The results revealed that administration of BPA significantly induce the testicular damage which was evident from the body and organ weight, sperm count, sperm motility, antioxidants enzymes level were significantly decreased and increased level of oxidative stress in rat testes. Interestingly, administration of lycopene with BPA intoxicated rats were found the body and organ weight, sperm count, sperm motility, antioxidant enzymes were significantly increased and decreased levels of oxidative stress parameters. Histopathological examination revealed that lycopene reduced testicular damages induced by BPA. This inevitably confirms that lycopene has a prominent role in preventing the testicular damage during treatment. In conclusion, BPA induced antioxidant and oxidative stress alteration lead to male infertility because of antioxidant potential of lycopene, ameliorates the changes which are induced by BPA.